PENERAPAN MEDIA MISTERI BOX UNTUK MENINGKATKAN HASIL BELAJAR PPKN DAN KEAKTIFAN SISWA DI KELAS III SDN RAPPOJAWA KOTA MAKASSAR - Nur Zahara Harun; Abdul Azis; Musdalifah Syahrir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The purpose of this study was to determine the improvement in PPKn learning outcomes and student activeness through the use of mystery box media in grade III of SDN Rappojawa, Makassar City. The research conducted was a classroom action research (CAR). This research was conducted in two cycles consisting of planning, implementation, observation, and reflection, which included four meetings. The subjects of this study were 21 grade III students of SDN Rappojawa, Makassar City, consisting of 11 boys and 10 girls. Data collection techniques were observation, testing (evaluation), and documentation. The data obtained were then analyzed using quantitative and qualitative descriptive analysis. The results achieved quantitatively are (1) Increased PPKn learning outcomes through the application of mystery box learning media for third-grade students at SDN Rappojawa, Makassar City experienced an increase where the average value obtained by students after taking the final test from cycle I to cycle II after the application of the learning model increased from 59.3 in cycle I to 87.9 in cycle II. The PPKn learning mastery of third-grade students at SDN Rappojawa, Makassar City also increased. In cycle I, from 9 (42.8%) students to cycle II as many as 21 (100%) students achieved learning mastery and classical learning mastery was achieved, namely 70%. (2) The increase in student activity through the application of mystery box learning media in third grade students at SDN Rappojawa, Makassar City experienced an increase where the percentage of student activity in cycle I was 8 students or 38% in the active category, 5 students or 24% in the less active category, and 8 students or 38% in the inactive category. While the percentage of student activity in cycle II was 17 students or 81% in the very active category, 4 students or 19% in the active category. The conclusion is that the mystery box media can improve PPKn learning outcomes and the activity of third grade students at SDN Rappojawa, Makassar City.